Pandemic Covid-19 Resilience in Improving Employee Performance at Mason Elephant Park and Lodge - Suarjaya, I Nyoman; Padmini, Putu Ayu Putri (Jurnal Manajemen Pelayanan Hotel, 2022)
This research is used to find out what strategies can be applied to improve employee performance at Mason Elephant Park and Lodge. Where employee performance is used as a research variable. There are 2 data collection techniques in this study, namely through literature study and questionnaires. This study is a type of quantitative data in the form of a questionnaire distributed to 100 employees at Mason Elephant Park and Lodge which was sampled through a simple random sampling technique from 340 total population of employees. The data analysis technique used in this research is using SWOT analysis. Where, from the results of the SWOT analysis, the Mason Elephant Park and Lodge company is in quadrant I position. So the SO strategy that can be focused is maintaining the composition of the number of employees who come from the local area and doing CSR in the village; improve technology support and services; and scheduling workforce training. Keywords: Employee performance, SWOT analysis, tourism.